Raised Triglyceride Level is A Risk Factor for Pre-Eclampsia - RAKHSHANDA REHMAN, SHAZIA NOOR, UZMA HUSSAIN, FAROGH ZAHRA, (Journal of Fatima Jinnah Medical University, 2018)
Objective: The objective of this study is to determine the elevated triglyceride level as a risk factor for pre-eclampsia. Study design: Analytical study: case control design. Place and duration of study: This study was conducted at the Department of Obstetrics and Gynecology Unit-I Fatima Jinnah Medical College/ Sir Ganga Ram Hospital, Lahore, during the period of six months (1-4-2009 to 31-09-2009). Subjects and Methods: One hundred and twenty pregnant women presenting to obstetrics and gynaecology unit-I, Sir Ganga Ram Hospital Lahore, through emergency as well as outdoor fulfilling the inclusion criteria were included in the study. Out of which sixty normotensive were at term and sixty with blood pressure ≥140/90mmHg and proteinuria +2 at ≥20 weeks of gestation. Fasting triglyceride level was carried out by standard kit method. Results: The mean age of patients in study group was 28.8±3.1 years and in control group were 28.7±3.1 years. The mean body mass index (BMI) in study group was 26.8±2.2 kg/m2 and in control group was 24.7±1.8 kg/m2. The mean serum triglyceride in study group was 195.1±32.8 mg/dl and in control group was 167.2±24.8mg/dl. In study group, 27 (45%) patients had raised serum triglyceride level and 33 (55%) patients had normal serum triglyceride level and in control group, 10 (16.7%) patient had raised serum triglyceride level and 50 (83.3%) patients had normal serum triglyceride level. Conclusion: It is concluded from this study that there is an association between raised serum triglyceride levels and pre-eclampsia as in our study 45% patients had raised serum triglyceride level while in control group serum triglyceride level was raised only in 16.7% patients.